Managing balanced development in India - Analysis of achieving provisions under Article 371 j for the special development of Hyderabad Karnataka - Mohammed, Moona (International Journal of Psychosocial Rehabilitation, 2024)
Addressing the regional imbalances is the biggest challenge in the management of thedevelopment. There are Regional Imbalances in development in India for a long time.Investment and efforts should be spread out evenly across various regions to ensurebalanced development of the country or a state. This article traces the history ofregional imbalances in India as it existed in Mughal and British period. Nanjundappacommittee report (2002) empirically established regional imbalances existedKarnataka, which is a Southern state in India. In order to rectify the backwardness ofthe Hyderabad Karnataka region, article 317 j was inserted in the Constitution ofIndia. This resulted in reserving certain share of jobs and educational opportunities inEducational Institutions to the persons belonging to the region. The amendment alsomandated allocating certain amount of funds for the regional development board.Since inception, the board was able to utilise Rs. 2961.47 crores out of the Rs.4621.76 crores allocated. Board was able to complete 73.82% of works approved sofar. The analysis in the paper shows that considerable progress has been made inidentifying and filling up the posts reserved for the regional level. Government hasbeen allocating exclusive funds to the Regional development board. However,utilisation of the funds and completion of works needs improvement.